Antibacterial activity against bacillus subtilis and antioxidant properties of methanol extracts from garcinia latissima miq. Leaves - Ambarwati, Neneng Siti Silfi; Elya, Berna; Malik, Amarila; Hanafi, Muhammad; Omar, Hanita (Innovare Academic Sciences Pvt. Ltd. India, 2018)
Objective: The objective of this study was to identify fractions with the highest antibacterial activity against Bacillus subtilis and to determine antioxidant activities and establish the chromatographic fractions as candidate antibacterial and antioxidant agents. Methods: Extracts were fractionated using column chromatography, and antibacterial activities were assayed by the analyses of inhibition zones and bioautography, as well as by broth microdilution techniques. Antioxidant activities were evaluated using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay. Results: The strongest antibacterial activity against B. subtilis (ATCC 6633) was observed with fractions B and C obtained in this research, with a minimum inhibitory concentration value of 312.5 μg/mL. The effective percentage (EP) value of crude extract at 10 μg/mL was 29.47±2.01%. Fractions C and D had greater EP values than the crude extract, whereas fraction D had the highest scavenging activity against DPPH free radicals (37.73±1.44%) when used at 10 μg/mL. The half effective concentration of the extract was 23.40 μg/mL, whereas that of the most active fraction D was 19.38 μg/mL and quercetin as positive control was 3.72 μg/mL. Conclusion: The present data confirm that fractions of methanol extract from Garcinia latissima Miq. leaves possess antibacterial and antioxidant activities. These observations may facilitate the development of antimicrobial phytomedicines with a wide spectrum of activities and standardized antioxidant properties.